Social Media Used by Government Institutions in Iceland: Application, Role and Aims - Einarsson, Már; Gunnlaugsdóttir, Jóhanna (Stjórnsýslustofnun, 2014)
The purpose of this research was to study the use and role of social media hosted by government institutions in Iceland. The research was conducted using quantitative and qualitative research methods. A survey was sent electronically to all government institutions in Iceland and semi-structured interviews were conducted with specialists working for institutions. No research has been conducted on this subject in Iceland before. It was therefore considered timely that a research was conducted on the use of social media in public institutions, with the intention of adding new knowledge to the field. No similar research from outside of Iceland was found, but this research was based on related studies and sources from abroad. A little less than half of government institutions used social media as part of their activities and Facebook and YouTube were most widely used. Popularity, circulation, usefulness and convenience were the most important factors when choosing social media. The majority of institutions had neither defined social media goals nor the role and responsibility of employees when using social media. The institutions placed strong emphasis on publishing adverts and news items on the institutions’ activities via social media pages and there were a considerable number of references to material on other web pages. Among other things the interviewees said that the purpose of using social media was information dissemination, reception of information, more visibility, the opening of institutions to the public and increased transparency. They talked about the importance of being informal on social media, but they also pointed out that there had been some fear among institutions of using them, in particular fear of employees showing a human side via social media. There was minimal use of original material on institutions’ social media pages, while institutions were quite systematic in posting material from their website through social media. Also, the public did not post much material on social media used by ...